Students’ Satisfaction at Night High School and Its Influence in School Dropout - Ramírez-Díaz, José Laurian (2018)
This paper presents an analysis on the satisfaction of night school students about their educational process, from the valuation they have of their own motivation, physical infrastructure facilities, and interpersonal relationships between students and teachers, specifically in the technical and professional education fields. All this aimed to analyze components that increase the feeling of well-being, and enhance the promotion and academic success based on criteria to prevent the school dropout. To do so, we conducted a factor analysis with information obtained from a questionnaire based on a Likert scale. The questionnaire was applied to a sample of 120 participants; with it, we identified some important indicators to be considered in actions to prevent dropout in adult students. The collected information was presented in statistical tables, which display indicators of satisfaction about infrastructure, teacher´s treatment, and student´s motivation.